The Influence of Service Quality and Trust on Loyalty Mediated by Satisfaction in Shopee Customers - Putri Yasshinta, Nerisa; Nadhira Ayu Setyaning , Alldila (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to examine the effect of electronic service quality and electronic trust on customer electronic satisfaction and electronic loyalty, as well as the mediating role of electronic satisfaction on the effect of electronic service quality and electronic trust on customer electronic loyalty. The population in this study were Shopee customers. The sample in this study was 150 respondents and was taken using convenience sampling. The data collection technique was carried out using a questionnaire. Data analysis was carried out using PLS-SEM. The results of the study showed that electronic service quality and electronic trust had a positive and significant effect on customer electronic satisfaction. Electronic service quality and electronic trust had a positive and significant effect on customer electronic loyalty. Electronic satisfaction plays a role in partially mediating the effect of electronic service quality and electronic trust on customer electronic loyalty.